Neurologic complications of HIV in the HAART era: where are we? - Monica M. Gomes da Silva (Brazilian Journal of Infectious Diseases)
Human immunodeficiency virus (HIV)-associated neurological complications continue to occur despite the development in antiretroviral treatment. New forms of old opportunistic infections and increased prevalence of neurocognitive disorders are the challenges that infectious diseases specialists face in daily clinic. How to screen and treat these disorders are subject of debate and new studies are underway to answer these questions. This review focuses on a brief discussion about opportunistic infections still present in late diagnosed HIV-infected patients and describes new forms of HIV-related neurological complications.